2021
DOI: 10.1002/cptc.202100176
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Excitation Polarized Field Drives Photoelectric Catalysis for Dye Degradation in a BaTiO3/CdS Heterojunction through Integration of Solar and Thermal Energy

Abstract: Efficient charges separation and transfer are considered to be the key factors to achieve high efficiency photoelectric catalysis. Herein, we proposed that the internal potential difference and the macroscopic polarization field of the homotype BaTiO3/CdS pyroelectric heterojunction can adjust the photoelectric catalytic performance to achieve degradation of methylene blue (MB) and rhodamine B (RhB) dyes. Under 20–50 °C hot–cold cycles, light and external bias, the catalytic rate of BaTiO3/CdS for MB is 4.82×1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…UV‐visible absorption spectra of BaTiO 3 , Ba 0.7 Sr 0.3 TiO 3 and Ba 0.7 Sr 0.3 TiO 3‐X are shown in Figure 5a and S5. The absorption edge of BaTiO 3 appears at about 391.2 nm, corresponding to the gap of 3.17 eV (the calculation process is shown in formula (2) of support information), which is roughly consistent with the reported results of BaTiO 3 [48,49] . After Sr doping, the absorption edge appears red shift to 403.9 nm.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…UV‐visible absorption spectra of BaTiO 3 , Ba 0.7 Sr 0.3 TiO 3 and Ba 0.7 Sr 0.3 TiO 3‐X are shown in Figure 5a and S5. The absorption edge of BaTiO 3 appears at about 391.2 nm, corresponding to the gap of 3.17 eV (the calculation process is shown in formula (2) of support information), which is roughly consistent with the reported results of BaTiO 3 [48,49] . After Sr doping, the absorption edge appears red shift to 403.9 nm.…”
Section: Resultssupporting
confidence: 87%
“…The absorption edge of BaTiO 3 appears at about 391.2 nm, corresponding to the gap of 3.17 eV (the calculation process is shown in formula (2) of support information), which is roughly consistent with the reported results of BaTiO 3 . [48,49] After Sr doping, the absorption edge appears red shift to 403.9 nm. The band gap is reduced to 3.07 eV, which is basically consistent with the report of Ba 0.7 Sr 0.3 TiO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…19 For CdS, the combination of CdS with other different semiconductors has been studied to enhance the pyroelectric properties of materials such as NaNbO 3 /CdS, 20 SnS/CdS, 13 and BaTiO 3 /CdS. 21 In addition, Zhang et al 22 found that CdS nanorods decorated with an organic molecule, 2-mercaptobenzimidazole (2MBI), can greatly enhance the pyroelectric properties and pyroelectric-induced charge separation. At the same time, the surface of CdS has few exposed active sites, limiting the photocatalytic activity, which can be increased by engineering an intimate interface with abundant active sites between a semiconductor and a cocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Therefore, the enhancement of hydrogen production by photo-electric catalysis water splitting through the pyroelectric effect of pyroelectric materials has attracted wide attention. 25 For example, Zhang et al 26 reported the combination of pyroelectric catalysis and photoelectrochemical catalysis based on NaNbO 3 nanocubes, which realized the energy collection of cold and hot alternate energy and solar energy, and provided reasonable design ideas for the effective design of new environmentally friendly photoelectrodes for PEC water splitting. As mentioned above, it is feasible to improve the photoelectrocatalytic performance by using the pyroelectric effect and combine solar energy, thermal energy and electric energy for water splitting to produce hydrogen.…”
Section: Introductionmentioning
confidence: 99%